Medical device specificities: opportunities for a dedicated product development methodology - Isa C. T. Santos (2012)
The medical sector, similarly to other industries as the aviation industry, has to comply with multiple regulations, guidelines and standards. In addition, there are multiple definitions for the expression medical device and, before entering the market, manufacturers must demonstrate their products safety and effectiveness. In such a complex and demanding environment it is crucial to know the particularities surrounding the product being developed in order to minimize the chances of a commercial flop. Thus, in this paper, the medical devices specificities are identified and the most relevant legislation is reviewed providing the foundations for a dedicated product development methodology.